John G. Sommer. Empowering the Oppressed: Grassroots Advocacy Movements in India. New Delhi: Sage Publications, 2001. 207 pages. Paperback. Price not given. (The Pakistan Development Review, 2002)
Advocacy movements all over the world have been quite instrumental in bringing about social change. The efforts of groups involved in such movements are directed towards realising the core human values of justice and equality by securing the human and civil rights of the poor, oppressed, and marginalised sections of society. Lately, many groups have realised that merely obliterating the effects of oppression, discrimination, and injustice is not enough—these efforts must be supplemented by attempts to address their root causes as well. Only by doing so, the constructive changes occurring in society owing to the struggle of these movements can become sustainable.